Survival with a Helping Hand: Campylobacter and Microbiota - Indikova, Ivana; Humphrey, Tom J.; Hilbert, Friederike (Frontiers in Microbiology, 2015)
Campylobacteriosis is the most important bacterial food-borne disease in the developed world. Consumption of chicken meat, beef or raw milk, direct contact with ruminants and exposure to contaminated surface water or even consumption of tap water have been identified as risk factors for human disease. However, the most important risk factor is consumption of and/or handling contaminated chicken. Campylobacter spp. are fastidious microorganisms but must somehow survive outside the host, especially in food and agricultural environments and also resist the innate and humoral immune responses inside the host. In this paper we hypothesize that other microorganisms in mixed populations with Campylobacter may act to improve survival outside the host and may also protect the pathogen against the intestinal immune system. Our evidence for this hypothesis is based on: 1. newly generated microbial community analysis; 2. the prolonged survival of Campylobacter in mixed species biofilms and in co-culture with environmental bacteria; 3. improved survival in amoebae and rumen fluid; 4. sulphur release and iron uptake systems within the intestinal lumen. This would make Campylobacter an exceptional food-borne pathogen. With this in mind, new strategies are necessary to combat Campylobacter along the total food chain.